Etalement Urbain Et Tensions Foncieres Dans Les Villages Peripheriques De Daloa (Centre-Ouest, Cote d’Ivoire) - Charles, Gouamene Didier; Raphael, Oura Kouadio; Sahoti, Ouattara (European Scientific Journal, ESJ, 2017)
The city of Daloa, located in the Ivorian west-centre, is experiencing a rapid spatial growth in recent years due to the acceleration of urbanization. This phenomenon, which should logically constitute an opportunity, because of the consumer market that it represents for the peri-urban villages, is becoming one of the causes of the tensions, then weakening social cohesion. The current urban dynamics cause the problem of space occupation by buildings and the destruction of natural and land resources around the city. Faced with this urban sprawl, which is increasingly aggressive and capable of swallowing up all the surrounding rural areas, the village communities express their concern over the transformation of their regions. In this framework, where the fear of the future has settled in the countryside and where land has become a major issue, the resulting competition for land is more than ever strengthened. This has resulted in land tensions that undermine their resilience faced with the scale of urbanization. The study, which is based on the dual quantitative and qualitative approach, aims to understand both the link between land tensions and urban spread and the perception and strategies developed by rural populations faced with urban pressure.